2019
DOI: 10.1063/1.5127692
|View full text |Cite
|
Sign up to set email alerts
|

EuPRAXIA – a compact, cost-efficient particle and radiation source

Abstract: Plasma accelerators present one of the most suitable candidates for the development of more compact particle acceleration technologies, yet they still lag behind radiofrequency (RF)-based devices when it comes to beam quality, control, stability and power efficiency. The Horizon 2020-funded project EuPRAXIA ("European Plasma Research Accelerator with eXcellence In Applications") aims to overcome the first three of these hurdles by developing a conceptual design for a first international user facility based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…is the light-like component u − of u, as well as the Doppler factor experienced by the particle, and is positive-definite [the first = in (6) follows from γ = dt/dτ , p z = mdz/dτ ]. We name s the light-like relativistic factor, or shortly the s-factor.…”
Section: Set-up and General Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…is the light-like component u − of u, as well as the Doppler factor experienced by the particle, and is positive-definite [the first = in (6) follows from γ = dt/dτ , p z = mdz/dτ ]. We name s the light-like relativistic factor, or shortly the s-factor.…”
Section: Set-up and General Resultsmentioning
confidence: 99%
“…2 In fact, huge investments aiming at the construction of table-top particle accelerators based on Wake Field Acceleration are being made all over the world. For instance, in Europe the large network of research centers "European Plasma Research Accelerator with eXcellence In Applications" (EUPRAXIA) has been created to develop the associated technologies and has just issued its expected Conceptual Design Report of reliable accelerators of this kind [6,7,8]. Among the present and future applications of accelerators we mention:…”
Section: Introductionmentioning
confidence: 99%
“…the latter inequality and (31) amount to the right inequality in (27b), which holds together with s(ξ, Z) ≥ 1. The right inequality in (29) follows from (11) and (25). From 2∆ (1)…”
Section: Generic Density Casementioning
confidence: 98%
“…The huge accelerating fields (three orders of magnitude larger than conventional RF field used in accelerators) require a high degree of control of the beam parameters to reach the same stability and reliability of conventional accelerators. At the moment, several solutions are being investigated [33], ranging from laser-to particle-driven accelerators. The two case studies reported in this section are representative of two typical cases.…”
Section: Plasma Based Particle Acceleratorsmentioning
confidence: 99%